Impact of glucocorticoid receptor polymorphism rs6198 on sepsis survival in a prospective multicenter cohort - Christoph Sombetzki; Lars Palmowski; Dominik Ziehe; Hartmuth Nowak; Tim Rahmel; Stefan Felix Ehrentraut; Patrick Thon; Jennifer Orlowski; Lars Bergmann; Michael Adamzik; Björn Koos; Katharina Rump; et al. (Scientific Reports)
Abstract The glucocorticoid receptor (GR), particularly its isoforms GRα and GRβ, plays a crucial role in modulating inflammatory responses. The rs6198 single nucleotide polymorphism (SNP) in the NR3C1 gene, which encodes GR, has been associated with adverse outcomes in various diseases due to its potential effect on GR isoform expression. This study aims to explore the impact of the rs6198 SNP in sepsis. Specifically, we tested the hypothesis that the presence of a particular genotype of the rs6198 SNP is associated with an increased 30-day mortality rate in patients with sepsis. This prospective, multicenter study included 204 ICU patients diagnosed with sepsis, as part of the Sepsis.Data.Net NRW cohort. Genotyping for rs6198 and immunofluorescence as well as quantification of GR expression were performed. Statistical analyses included Hardy–Weinberg equilibrium, Kaplan–Meier survival analysis, log-rank tests, multivariate Cox regression, and logistic regression. Genotyping for the rs6198 SNP identified 137 patients (67%) with the TT- and 67 (33%) with CC/CT-genotype. Patients with the TT-genotype had a 30-day survival rate of 65% (89 of 137 patients), which was significantly lower than the 82% survival rate (55 of 67 patients) observed in the patients with the CC/CT-genotype (p = 0.006). A multivariate Cox regression analysis, adjusted for age, SOFA and SAPS2 score, and selected laboratory values, revealed that the TT-genotype was independently associated with an increased risk of death (HR 3.56, 95% CI 1.22–10.38, p = 0.02). Subgroup analysis demonstrated a particularly pronounced impact among patients with initially high disease severity (HR 6.16, 95% CI 1.66–22.80, p = 0.007). In addition, expression analysis revealed a significantly higher presence of GRα in patients with the TT-genotype compared to those with CC/CT genotype (p = 0.023). Increased GRα expression was also associated with higher 30-day mortality (HR 2.38, 95% CI 1.48–3.82, p < 0.001). The rs6198 SNP in the NR3C1 gene is associated with 30-day mortality in sepsis patients and correlates with increased expression of the GRα isoform. These results highlight the TT-genotype as a potential risk marker. Further research is needed to clarify the causal mechanisms and explore personalized therapeutic implications in sepsis management.